Gwarowe nazwy ubiorów w „Słowniku warszawskim” - Borejszo, Maria (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The article discusses slang lexis related to garment names, documented in Słownik języka polskiego [Dictionary of Polish Language] by Jan Karłowicz, Adam Kryński, and Władysław Niedźwiedzki (vols. I–VIII, Warszawa 1900–1927). Many of the words are unknown to literary Polish of the first decades of the 20th century, and some differ in their pronunciation, structure, or meaning from garment dictionary used in standard Polish. As the research suggests, the slang material documented in the dictionary is not only rich, but also varied in terms of form and meaning. Characteristically, many words are unstable. Słownik warszawski contains particularly many words for outer garments. Unfortunately, the editing layout of entries in the dictionary makes it impossible to localize the origin of each garment name, and consequently to link it to a particular slang. The explanations of words in the dictionary are usually very short, which often not enough to reconstruct the look and purpose of a garment.